2013 San Antonio Breast Cancer Symposium. (June 2014) - Rossi, Valentina; Martinello, Rossella; Aversa, Caterina; Montemurro, Filippo
Abstract : The San Antonio Breast Cancer Symposium is considered by researchers and physicians involved in breast cancer management as one of the most important international events on the subject. A dense program of plenary presentations of novel findings, main lectures, poster discussions and displays, it encompasses all the aspects of the rapidly evolving field of breast cancer research and treatment. This article briefly summarises some of the presentations that are expected to have an impact on the medical treatment of breast cancer.